2019
DOI: 10.1177/0023830919875481
|View full text |Cite
|
Sign up to set email alerts
|

Gemination in Northern versus Central and Southern Varieties of Italian: A Corpus-based Investigation

Abstract: It is often claimed that patterns of gemination are different across varieties of Italian. In particular, northern speakers are sometimes said to degeminate, or to produce shorter geminates than central and southern speakers. However, experimental data proving such claims is largely missing. In this article, we perform an analysis of the CLIPS corpus with the aim of comparing gemination for northern versus central and southern speakers of Italian. The analysis of different data types (target words in isolated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…The bilinguals were native speakers of central and southern varieties of Standard Italian. Gemination is well documented in these varieties of Italian, where geminate consonants are phonetically about twice as long as corresponding singletons (Bertinetto & Loporcaro, 2005; Giordano & Savy, 2012; Mairano & De Iacovo, 2020, found similar durations in contemporary northern varieties). The bilingual participants had lived in Italy at least until high school graduation, and had been living in England for an average of 8 years ( SD = 6).…”
Section: Methodsmentioning
confidence: 91%
“…The bilinguals were native speakers of central and southern varieties of Standard Italian. Gemination is well documented in these varieties of Italian, where geminate consonants are phonetically about twice as long as corresponding singletons (Bertinetto & Loporcaro, 2005; Giordano & Savy, 2012; Mairano & De Iacovo, 2020, found similar durations in contemporary northern varieties). The bilingual participants had lived in Italy at least until high school graduation, and had been living in England for an average of 8 years ( SD = 6).…”
Section: Methodsmentioning
confidence: 91%
“…Previous studies [7 , 8] suggested in fact that the Roman accent, although distinctive, is phonologically close to Standard Italian: it shares with Standard Italian a same phoneme inventory and phonotactic rules and shows similar behavior with respect to consonant gemination, in particular when spoken by educated people [8] , although, as also pointed out by Payne in [7] , the concept of Standard Italian is somewhat idealized. As a matter of fact, a progressive standardization of the Italian language was observed in a recent and comprehensive study on gemination across regional variations of Italian [9] . Note that a recent Italian read speech database also made use of speakers from Rome [10] , and led to new insights on lexical vs. syntactic gemination [4] .…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 95%
“…Given the long-standing contact between Standard Italian and dialects, it is likely that intonational patterns of ND are transferred to NI, parallel to what has been observed in other varieties [15], besides possible levelling effects which are known to affect dialects in the direction of standard languages [25,26]. A relevant case in this sense is provided by information-seeking yes-no questions in ND, whose tune seems to display the same rise-fall L*+H HL-L% pattern observed in NI [4,5,6], in which L*+H and HL-mark the beginning and the end of the focus constituent -Figures 1-2.…”
Section: Question and Statement Tunesmentioning
confidence: 99%